The Nitric Oxide Donor, S-Nitrosoglutathione, Rescues Peroxisome Number and Activity Defects in PEX1G843D Mild Zellweger Syndrome Fibroblasts - Liu, Yidi; Weaver, Ceileigh M.; Sen, Yarina; Eitzen, Gary; Simmonds, Andrew J.; Linchieh, Lilliana; Lurette, Olivier; Hebert-Chatelain, Etienne; Rachubinski, Richard A.; Di Cara, Francesca (Frontiers in Cell and Developmental Biology, 2021)
Peroxisome biogenesis disorders (PBDs) are a group of metabolic developmental diseases caused by mutations in one or more genes encoding peroxisomal proteins. Zellweger syndrome spectrum (PBD-ZSS) results from metabolic dysfunction caused by damaged or nonfunctional peroxisomes and manifests as a multi-organ syndrome with significant morbidity and mortality for which there is no current drug therapy. Mild PBD-ZSS patients can exhibit a more progressive disease course and could benefit from the identification of drugs to improve the quality of life and extend the lifespan of affected individuals. Our study used a high-throughput screen of FDA-approved drugs to identify compounds that improve peroxisome function and biogenesis in human fibroblast cells carrying the mild PBD-ZSS variant, PEX1G843D. Our screen identified the nitrogen oxide donor S-nitrosoglutathione (GSNO) as a potential therapeutic for this mild form of PBD-ZSS. Further biochemical characterization showed that GSNO enhances both peroxisome number and function in PEX1G843D mutant fibroblasts and leads to increased survival and longer lifespan in an in vivo humanized Drosophila model carrying the PEX1G843D mutation. GSNO is therefore a strong candidate to be translated to clinical trials as a potential therapeutic for mild PBD-ZSS.